The Autonomous Mind: The Right to Freedom of Thought in the Twenty-First Century - McCarthy-Jones, Simon (Frontiers in Artificial Intelligence, 2019)
To lose freedom of thought (FoT) is to lose our dignity, our democracy and our very selves. Accordingly, the right to FoT receives absolute protection under international human rights law. However, this foundational right has been neither significantly developed nor often utilized. The contours of this right urgently need to be defined due to 21st century threats to FoT posed by new technologies. As such, this paper draws on law and psychology to consider what the right to FoT should be in the 21st century. After discussing contemporary threats to FoT, and recent developments in our understanding of thought that can inform the development of the right, this paper considers three elements of the right; the rights not to reveal one’s thoughts, not to be penalized for one’s thoughts, and not to have one’s thoughts manipulated. The paper then considers, for each element, why it should exist, how the law currently treats it, and challenges that will shape it going forward. The paper concludes that the law should develop the right to FoT with the clear understanding that what this aims to secure is mental autonomy. This process should hence begin by establishing the core mental processes that enable mental autonomy, such as attentional and cognitive agency. The paper argues that the domain of the right to FoT should be extended to include external actions that are arguably constitutive of thought, including internet searches and diaries, hence shielding them with absolute protection. It is stressed that law must protect us from threats to FoT from both states and corporations, with governments needing to act under the positive aspect of the right to ensure societies are structured to facilitate mental autonomy. It is suggested that in order to support mental autonomy, information should be provided in autonomy-supportive context and friction introduced into decision making processes to facilitate second-order thought. The need for public debate about how society wishes to balance risk and mental autonomy is highlighted, and the question is raised as to whether the importance attached to thought has changed in our culture. The urgency of defending FoT is re-iterated.